The impact of disturbance on tree reproductive ecology, and some implications for regeneration and conservation - Gazoul J.; Hutacharern C.; Liston K.; Boyle, T.J.B. (1997)
Research on the impact of disturbance on pollination and seed predation processes in the deciduous dipterocarp forests (DDF) of Thailand had produced interesting results that relate to the conservation of deciduous forests in general, and Huay Kha Khaneg Wildlife Santuary (a World Heritage Site) in particular. The DDF's of mainland SE Asia, which have suffered various degrees of disturbance in recent decades, represent an important habitat that supports a wide range of plants and animals. Our objective is to investigate the impact of past and continuing anthropogenic disturbance on the reproductive ecology of the dominant tree species, thereby assessing the resilience of the forest community as a whole. Shorea siamensis, a widespread canopy tree, was studied at three locations of differing disturbance intensity in HKK. Disturbance pressures are primarily logging and fire. The flowers of S. siamensis are self-incompatible and pollinated by small bees. Stigma pollen load, indicative of pollinator activity, and pollen tube growth, reflecting pollen compatibility, were reduced in disturbed low density areas. Fruit set at all sites was low relative to flower number, but particularly so at the disturbed site. Damage by insects, mammals and fungi to developing fruit was evident, but did not significantly alter the pattern of viable fruit production across sites. Resources and pollen are generally considered to limit fruit set. Soil nutrient across sites at HKK were similar, and artificial cross-pollination resulted in a four-fold increase of fruit production, making resource limitation of fruit set unlikely. Initially it appears that pollen does not limit fruit set either, as most flowers at all sites receive pollen, but due to the self-incompatibility mechanism, viability of pollen is not assured. We conclude that trees in the disturbed site have reduced pollination success due to disrupted flow of compatible pollen caused by localized foraging behaviour of the small bee pollinators and exessive tree to nearest neighbour distances. Our results indicate that trees at low density receive fewer compatible pollen, thereby limiting fruit set and, potentially, population recovery. Thus S. siamensis may be subject to the Allele effect (Burgman et al. 1992), where population viability is reduced disproportionately with a decline in size (Kunin 1993; Lamont et al. 1993). Reduction of tree density beyond a critical threshold might have a run-away effect leading to local extinction, with obvious implications for biodiversity and land use.